Is 50/MWh solar for real? Falling project prices and rising capacity factors drive utility‐scale PV toward economic competitiveness. (22nd May 2015) - Bolinger, Mark; Weaver, Samantha; Zuboy, Jarett
Abstract: Recently announced low‐priced power purchase agreements (PPAs) for US utility‐scale photovoltaic (PV) projects suggest 50/MWh solar might be viable under certain conditions. To explore this possibility, this paper draws on an increasing wealth of empirical data to analyze trends in three of the most important PPA price drivers: upfront installed project prices, operations, and maintenance (O&M) costs, and capacity factors. Average installed prices among a sample of utility‐scale PV projects declined by more than one third (from 5.8/WAC to 3.7/WAC ) from the 2007–2009 period through 2013, even as costlier systems with crystalline‐silicon modules, sun tracking, and higher inverter loading ratios (ILRs) have constituted an increasing proportion of total utility‐scale PV capacity (all values shown here are in 2013 dollars). Actual and projected O&M costs from a very small sample of projects appear to range from 20–40/kWAC ‐year. The average net capacity factor is 30% for projects installed in 2012, up from 24% for projects installed in 2010, owing to better solar resources, higher ILRs, and greater use of tracking among the more recent projects. Based on these trends, a pro‐forma financial model suggests that 50/MWh utility‐scale PV is achievable using a combination of aggressive‐but‐achievable technical and financial input parameters (including receipt of the 30% federal investment tax credit). Although the US utility‐scale PV market is still young, the rapid progress in the key metrics documented in this paper has made PV a viable competitor against other utility‐scale renewable generators, and even conventional peaking generators, in certain regions of the country. Published 2015. This article is a U.S. Government work and is in the public domain in the USA. Abstract : Recent power purchase agreements for utility‐scale photovoltaic (PV) projects in the USA suggest 50/MWh solar is viable under certain conditions (including receipt of the 30% federal investment tax credit). This paper draws on an increasing wealth of empirical data to document progress in installed prices, operating costs, and capacity factors among utility‐scale PV projects. It then uses a pro forma financial model to demonstrate that aggressive‐but‐achievable inputs drawn from the empirical data do indeed support 50/MWh solar.